The role of environmental sustainability and physical fitness in enhancing lifespan - Djurayeva Mahasti; Niyazova Sitora; Niyazova Gulbahor; Mukhitdinova Nigora (E3S Web of Conferences)
Environmental problems such as climate change, industrialization, and urbanization pose significant challenges to human health and natural habitats. Adverse weather events, including air pollution, rising temperatures, and extreme weather conditions, are contributing to a decline in environmental quality and public health. This study aims to explore the integration of environmental sustainability principles with physical fitness to enhance human health and longevity. It seeks to identify innovative methods for incorporating ecological principles into fitness training and educational settings. A comprehensive review was conducted to assess existing strategies that combine environmental sustainability with physical education. The study analyzed various educational programs, fitness initiatives, and their impact on both health and environmental awareness. The findings highlight several effective approaches to merging sustainability with fitness training. Key strategies include incorporating outdoor physical activities that promote environmental stewardship, developing curricula that emphasize both fitness and ecological responsibility, and implementing school programs that encourage sustainable practices in physical education. Integrating environmental sustainability with physical fitness can provide dual benefits for health and the environment. This approach not only promotes physical health but also contributes to creating a more sustainable future.